The Effect of a Severe Plastic Deformation by Groove Pressing on the Grain Structure of the Al-Mg Alloy - Moskvichev E. N. Evgeny; Skripnyak V. V. Vladimir; Lychagin D. V. Dmitry Vasilievich; Krasnoveikin V. A. Vladimir (2017, 2017)
Title screen